A revision of the rare Strumigenys mnemosyne (Formicidae; Myrmicinae) group using micro-CT scanning, with the description of three new species, and the virtual repair of a broken paratype - Matthew T. Hamer; Julian Katzke; Kit Lam Tang; André Ibáñez Weemaels; Francisco Hita-Garcia; Evan P. Economo; Benoit Guénard (PLoS ONE, 2025)
The ant genus Strumigenys is both species rich, with over 800 species described, and morphologically diverse. The Strumigenys mnemosyne species group, a collection of small and infrequently collected Strumigenys known from across the Asian tropics and subtropics is revised. X-Ray microcomputed tomography alongside traditional microscopy is used describe three new species, S. liui sp. nov., S. marmorata sp. nov., and S. rimdahli sp. nov., increasing the number of species within the group to eight. Further, micro-CT scans of the worker and gyne caste of S. mazu are produced, providing the first morphological description for the later caste. Owing to specimen damage obtained during specimen transportation for one of the type specimens used within this study, the utility of 3D models to reconstruct broken type material is explored. Updated distributions and dichotomous keys are also provided for the group.